Review of N. Theotokas’s Ο βίος του στρατηγού Μακρυγιάννη: Απομνημόνευμα και Ιστορία [The life of General Makriyannis: memoir and history] - Andriakaina, Eleni (Historein, 2013)
Νikos Theotokas, Ο Bίος του στρατηγού Μακρυγιάννη:Απομνημόνευμα και Ιστορία [The life of General Makriyannis: memoir and history], Athens: Vivliorama, 2012. 549 pp.